The experiences of patients receiving care from nursing students at a Dedicated Education Unit: A phenomenological study. Issue 5 (September 2015) - Eskilsson, Camilla; Carlsson, Gunilla; Ekebergh, Margaretha; Hörberg, Ulrica
Abstract: The purpose of this study is to describe how patients perceive being cared for by student nurses, in a clinical context in the form of a Dedicated Education Unit (DEU). The study has been performed with a Reflective Lifeworld Research (RLR) approach grounded in phenomenology. Lifeworld interviews were conducted with patients who had received care from student nurses on an orthopaedic DEU and data have been analysed for meanings. The findings reveal how patients experience to be carried along as a part of the students' learning process. This is described in more detail via the constituents: a mutual invitation to participate, the importance of genuine encounters, and essential support . Patients experience both a stable and a less stable care in a learning environment and it is thus essential for them to be invited to be a part of both the students' learning process and their own health process. The findings also highlight the key role of the supervisors for patients' sense of security. Finally there are indications that concepts such as DEU with a lifeworld-led didactic, based on reflection on both the patients' stories and the students' experiences, can create learning environments that support patients' health processes and also students' learning processes. Highlights: Patients need to be invited to be a part of students' learning process as well as their own health process. Supervisors play a crucial role in stabilizing care in order to make patients feel secure and comfortable. Students' learning attitude contributes to patients' wellbeing. The interaction between students, supervisors and patients plays an essential role in patients' wellbeing.